Metabolic pathways of Alternative Lengthening of Telomeres in pan-carcinoma - Isaac Armendáriz-Castillo; Jennyfer García-Cárdenas; Pamela Espinosa; Katherine Hidalgo-Fernández; Lizbeth Peña-Zúñiga; Ronie Martínez; Juan Moromenacho; Andrés Herrera-Yela; Jonathan Cruz-Varela; Anilú Saucedo-Sariñana; María-Esperanza Cerdán; Andrés López-Cortés; et al. (PLoS ONE, 2025)
Alternative Lengthening of Telomeres (ALT) is a telomerase-independent mechanism deployed by several aggressive cancers to maintain telomere length. This contributes to their malignancy and resistance to conventional therapies. In prior studies, we have identified key proteins linked to the ALT process using multi-omic data integration strategies. In this work, we combined metabolomic datasets with our earlier results to identify targetable metabolic pathways for ALT-positive tumors. 39 ALT-related proteins were found to interact with 42 different metabolites in our analysis. Additional networking analysis revealed a complex interaction between metabolites and ALT-related proteins, suggesting that pan-cancer oncogenes may have an impact on these pathways. Three metabolic pathways have been primarily related with the ALT mechanism: purine metabolism, cysteine and methionine metabolism, and nicotinate and nicotinamide metabolism. Lastly, we prioritized FDA-approved drugs (azathioprine, thioguanine, and mercaptopurine) that could target ALT-positive tumors through purine metabolism. This work provides a wide perspective of the metabolomic pathways associated with ALT and reveals potential therapeutic targets that require further experimental validation.